Environmental assessment of water and soil quality in the Vientiane Plain, Lao PDR - Brindha, Karthikeyan; Pavelic, Paul; Sotoukee, T. (Elsevier, 2019)
A water and soil quality baseline study was carried out across the ~ 4500 km2 Vientiane Plain in Lao PDR. Eight water quality and nine soil parameters were analysed using field kits at 95 sites in March 2015. Elevated electrical conductivity and chloride were apparent at two sites due to geogenic leaching from the marine rock-salt present in some areas. Groundwater was acidic in most locations. Nitrate and faecal contamination were also observed from nitrogenous fertilizers (diffuse) and from leaky sewage pits (localised) respectively. Soil quality is neither nutrient deficient nor does it pose a threat to plant growth. Where groundwater is used for drinking, removal of bacterial contamination by simple filtration or boiling is sufficient. In the absence of a functional monitoring network in the Vientiane Plain, periodic surveys of this kind should be performed. The results should be made widely available to the relevant government departments and other stakeholders for better management of the land and water resources.